KAJIAN RELEVANSI GAMBAR DENGAN ISI BERITA PADA PROGRAM SEPUTAR SUMATRA BARAT DI ANTARA TV BIRO PADANG - Vicia Dwi Prakarti; Mahdi Bahar; Rosta Minawati (Institut Seni Indonesia Padang Panjang, 2017)
ABSTRACT This research discusses the relevancy of picture with news content that’s in the form of news script produced by the media of LKBN ANTARA TV, West Sumatra Bureau in Padang. LKBN ANTARA TV, West Sumatra Bureau is the news office of West Sumatra Bureau that exists under the central LKBN ANTARA TV in Jakarta. ANTARA news office belongs to Indonesia government. News aired consists of state news and community news. In television news, the picture becomes the main element in delivering information followed by narration/script as its support. The linkage between pictures with narration delivered must be understood by the viewers. It is done by ensuring the accuracy of taking moments by following the standard of shooting television news such as size shot, camera movement, camera angle, composition, sequence, and continuity. The picture of television news is supported by information obtained with a script that corresponds to the LKBN ANTARA format of news. The method used in this research was qualitative method (descriptive analysis) namely utterance, writing, and behavior that could be observed from the person or the subject itself described and analyzed by directly observing the teamwork process of ANTARA TV – West Sumatera. The author then analyzed news from the program of Seputar Sumatera Barat that had been aired through observation, interview, and documentation related to the research. The linkage between pictures resulted by news in the program of Seputar Sumatera Barat produced by LKBN ANTARA TV – West Sumatera bureau with the script or narration, still depends on producer’s involvement in determining that linkage. It is because the creative team of ANTARA TV-West Sumatera still maintains the criteria and character of central LKBN ANTARA. Keywords: The Picture of Television News, News Content, the Program of Seputar Sumatera Barat, LKBN ANTARA TV – West Sumatera